Language Development in Early Childhood: Psycholinguistic Approaches to English Language Education - Rhamadanty, Tirta; Ulum, Miftahul (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This article discusses the importance of understanding language development at an early age and how a psycholinguistic approach can provide a strong foundation in designing effective English language education for children at this crucial stage in their lives. The approach in this article involves analyzing the literature and tracing empirical studies related to language development in early childhood using psycholinguistic approaches. Data were analyzed to explore the role of this approach in English language learning at this critical developmental stage. And the result is that the integration of psycholinguistic approaches in children's English education at an early age shows great potential in facilitating language development effectively. By understanding and applying psycholinguistic principles, educators can create a supportive and meaningful learning environment, enabling children to better achieve their language potential.